A Review of Literature on Using Social Media to Learn English in A Relaxed and Convenient Manner - Nurjannah, Lydia; Afrianti, Mita; Nazly, Rafi; Safitri, Yuslia; Ihsan, Muhammad Taufik (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
We often hear the media as a means of communication, or more commonly referred to as